Pendekatan dan Langkah Praktis untuk Menjaga Keseimbangan Akademik dan Pekerjaan pada Strategi Efektif Menghadapi Risiko bagi Siswa yang Ingin Menjalani Kuliah Sambil Kerja - Ferdina Wati Ningsih; Adil Gunawan Zega; Sela Agustin; Shilvy Dita Aryani (Jurnal PKM Manajemen Bisnis, 2026)
Balancing academic responsibilities and work commitments is a significant challenge for students who plan to pursue higher education while working, requiring early preparation and awareness of potential risks. This community service activity aimed to provide practical approaches and strategies for maintaining academic-work balance and to equip students with knowledge and skills to manage risks effectively when studying while working. The activity was conducted at SMK Perguruan Rakyat 1 Jakarta on August 28, 2025, involving ten facilitators, consisting of students and lecturers from Universitas Pamulang, and 30 twelfth-grade students as participants. The implementation followed three stages: preparation, execution, and reporting. Methods included interactive lectures, practical exercises, group discussions, and question-and-answer sessions, all designed to share knowledge and real-life experiences regarding self-readiness, time management, and risk awareness. The activity successfully enhanced participants’ understanding of the challenges and potential risks associated with balancing work and study, enabling them to develop practical strategies for task prioritization, effective time management, and maintaining academic performance while working. Active participation and reflection during discussions fostered greater preparedness for future academic and professional responsibilities, encouraging students to make informed decisions and anticipate challenges in their dual role as students and workers.